Online labour markets: an inquiry into oDesk providers. (1st October 2010) - ,
Abstract : This study is an institutional ethnography of oDesk workers. The research makes use of an online questionnaire and semi-structured interviews to identify the ways in which the oDesk platform functions as the medium and expression of the activities of online workers. I analyse the marketplace along the structural dimensions of visibility, community, and economics and conclude by arguing that these structures are recursively ordered through various activities occurring as part of the contingent reproduction of the oDesk Marketplace.